O uso de celebridades no endosso de marcas globais e locais: um experimento com marcas esportivas - Brandão, Mariana Hammel (2016)
What is common among individuals is the fact that all are consumers and their consumption decisions affect the economic environment in the local and global level. So to Schiffman and Kanuk (2000), consumer behavior is a bit of much importance for marketing. In a globalized market, it is increasingly important to understand the dimensions that balance consumer preferences between global and local brands (Schuiling & Kapferer, 2004; Ritzer, 2007). Much of the sales of sporting goods has been influenced by the endorsement of celebrities and athletes in the sport, which can impact the consumer's attitude toward advertising, brand and purchase intent (Carlson, Donavan, & CUMISKEY, 2009; Dix, Phua, & Pougnet, 2010; Goldsmith, Lafferty, & Newell, 2000; Lear, Runyan, & Whitaker, 2009). Considering the celebrity endorsement and brand studies, this work has as main objective to verify the impact of celebrity endorsement with the intention of buying products from global and local brands. The specific objectives are: i) verify that the celebrity endorsement impacts the intention of buying products from global and local brands; ii) identify the type of celebrity (global and local) impacts at different levels, the intention of buying products from global and local brands, considering the involvement with the product; iii) analyze the impact of celebrity endorsement with the intention of buying products from global and local brands, considering ethnocentrism. To answer the proposed problem, an investigation was carried out with the quantitative methodology and designed an experiment that allowed to understand the relationships of cause and effect between the study variables. Experiment participants were 244 Brazilian consumers. Respondents were divided into 6 groups, and 2 were control groups and 4 were experimental groups. Through the experiment, it was observed that the prestige of global brand more influence on purchase intent than the celebrity endorsement. Added to this, there was no statistical evidence that the global celebrity impacts more than the local celebrity. Finally, we discuss the results and offer up possibilities for future studies.